Analisis Pembelajaran Matematika Materi Bangun Ruang Kubus dan Balok dengan Menggunakan Model Konstruktivisme Berbasis Lingkungan - Abdillah Halimi; Wijonarko Wijonarko; Ferina Agustini (Universitas Pendidikan Ganesha, 2021)
This research is motivated by the students' scores in learning mathematics on the subject of cube and block shapes and students' interest in mathematics. This study aims to analyze the model of environmental-based constructivism in mathematics learning materials for building blocks and cubes in elementary schools. The design of this research is a quantitative descriptive research design that is directed to analyze the application of the environmental-based constructivism learning model conducted by teachers in mathematics. Interview, observation, and documentation methods are data collection techniques used by researchers. Validation of data using triangulation of sources and techniques. While the data analysis technique is by collecting, reducing, presenting, and drawing conclusions of data. The results showed that there was a fairly good increase from 10 students who scored well to 18 students who had good grades so that if the percentage was made, it was 78,3% for students with good grades and 21,7% for children whose grades were not good or not. can meet the KKM. Based on the results of these studies, it can be concluded that the use of environmental-based constructivism learning models can influence student learning outcomes well.